(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Physical education (PE) is considered key to empowering young people for an active lifestyle. Europe is characterised by heterogeneous educational concepts and curricular landscapes. The concept of physical literacy (PL; Whitehead, 2001) has gained international attention in recent years. PL integrates physical, cognitive, and affective capabilities for lifelong physical activity (IPLA, 2017), advocating for a holistic empowerment to physically active lifestyles (Edwards et al., 2017). Despite the WHO (2018) promoting PL in its global action plan on physical activity (GAPPA), it remains unclear to what extent European countries currently meet the criteria of a ‘PL-inspired PE’. The aim of this study is to assess the fulfilment of core criteria for PL-inspired PE across Europe. Methods: Through a targeted literature review and iterative expert consultation, 15 criteria for ‘PL-inspired PE’ were developed and projected onto a 5-point Likert scale (e.g. student-centred vs. standard-oriented teaching; exploration vs. perfection orientation). Experts from 40 European countries evaluated these criteria using a four-eyes principle. Descriptive statistics assessed the fulfilment of the criteria. General linear models determined significant differences between the four European regions (Nordic, Southern, Western, Central/Eastern Europe) and between Anglophone and non-Anglophone countries. Exploratory correlations were calculated between PL compatibility and country-specific educational attainment (PISA) and human development indicators (HDI). Results: The 15 criteria showed satisfactory internal consistency (α = .86). The mean values for the ‘PL-inspired PE’ criteria clustered around the mid-point, indicating only a slight overall tendency towards a PL-affirming PE (0.31–0.75). Nordic countries showed the highest compatibility (mean (M) = 3.97, standard deviation (SD) = 0.54), differing significantly from Central/Eastern European countries (M = 3.04, SD = 0.60). Significant exploratory correlations were found between PL compatibility and educational attainment (r = .43, p = .006) and the HDI (r = .32, p = .043). Conclusion: The results illustrate the heterogeneity of curriculum-supported PE regarding its compatibility with the globally promoted PL concept. PE pedagogy in Europe should strengthen exchange, considering different cultural perceptions. The Nordic countries, viewed as advanced in the PL development process, are particularly relevant for international research. Keywords: Transformation, physical education, curricula, comparison, Europe